KOREKSI RADIOMETRIK METODE TOP OF ATMOSPHERE (ToA) CITRA LANDSAT 8 SECARA OTOMATIS DAN MANUAL - , RENNY DWI I. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is about radiometric correction of Landsat 8 imagery using Top of Atmosphere (ToA) method an automatic and manual processing. The purpose of Radiometric correction is to eliminate errors value of the digital number caused by difference of sun elevation angle when recording. process of ToA correction Landsat 8 having reference the formula made by USGS which changing the value of the digital number to reflectance values afterwards carry out the sun elevation angle correction. Image processing is done by two different processing manually is based GUI (Graphical User Interface) using software ERMapper 7.0 and automated is based programming languages using automation software _LDCM_tiff2ers_L1T designed by LAPAN. This processing is done in order to determine how to process image comparison in terms of the processing stage to the time needed to make corrections ToA. The results obtained by the Landsat 8 comparison between before and after the process ToA correction either manually or automatically is in terms of visual images, histograms, and the mean value of the visual image which does not show any significant difference or almost the same, while seen from the histogram and the mean values are significant differences that can be seen through the digital number images. In terms of automatic processing more efficient in terms of time and processing compared to manual processing, but to know the basic concepts ToA correction processing is better done by manually using software ERMapper.